A short review of popliteal artery entrapment syndrome - Hideaki Obara, MD; Prem Chand Gupta, MD; Lewis Levien, MD; Pradeep Mistry, MD; Venkatesh Bollineni, MD; Palma M. Shaw, MD (JVS-Vascular Insights)
Background: Popliteal artery entrapment syndrome (PAES) is a rare cause of lower limb ischemia, typically affecting young adults. Case Report: This case report describes a 22-year-old man with severe left calf claudication due to type II PAES, confirmed by imaging. Surgical treatment involved resection of the aberrant gastrocnemius muscle and popliteal artery reconstruction using the great saphenous vein. Postoperative recovery was uneventful, with complete symptom resolution and no recurrence at 2-year follow-up. Conclusions: PAES should be considered in young patients with unexplained claudication, and surgery offers effective long-term outcomes. This article also briefly discusses the classification, diagnosis, and treatment strategies for PAES.